Comparison Study of Vibration Control Effects between Suspended Tuned Mass Damper and Particle Damper - Zheng Lu; Dianchao Wang; Peizhen Li (Shock and Vibration)
The vibration control performance and its influencing factors of a tuned mass damper and a particle damper are examined by a single degree of freedom structure with such devices. The vibration control effects between these two dampers are also investigated. Increasing the mass ratio of the damper can improve the damping effects; under the condition of tuning frequency, the damping effects are remarkable. However, the more the deviation from the tuned frequency, the less controlling effects can be obtained. The damping effect of a particle damper is generally better than that of a tuned mass damper. For this test model, the particle damper can improve primary structure’s equivalent damping ratio 19 times to the original one’s, while the tuned mass damper can be 13 times. The reason lies in the fact that the particle damper can dissipate input energy by tuning mass, collision, impact, and friction between particles and the container and the momentum exchange effects between the secondary damper mass and the primary structure.